GEOSPATIAL ANALYSIS OF MARITAL DISSOLUTION IN NIGERIA - Arigbede, Y.A (FUDMA Journal of Earth and Environmental Sciences, 2025)
Marital dissolution remains a critical socio-demographic issue in Nigeria, with significant regional disparities in divorce and separation rates across the country’s six geopolitical zones. This study employs a geospatial approach to examine the patterns and socio-economic implications of marital dissolution using data from the Nigeria Living Standard Survey (NLSS) 2018/2019 and the Nigeria Demographic and Health Survey (NDHS) 2018. The findings reveal that marital dissolution rates (MDRs) vary significantly by region, with the South-South zone recording the highest MDR (7.2%), while the North-West reports the lowest (1.3%). The study identifies several key factors influencing divorce trends, including educational attainment, economic conditions, cultural practices, and religious beliefs. Divorce is highly stigmatised in the North, where women often face economic hardship and social exclusion. In contrast, in the South-West and South-South, rising financial independence among women and changing gender roles contribute to increased MDRs. The study also highlights the impact of urbanisation, polygamous marriages, early marriage practices, and economic instability in shaping marital outcomes. Based on these findings, the study recommends targeted policy interventions, including legal reforms, economic empowerment initiatives, and public awareness campaigns, to mitigate the adverse effects of marital dissolution and promote stable and equitable marital relationships across Nigeria’s diverse regions.